Major haemorrhage following vascular injury during exchange of cardiac pacemaker leads. Issue 1 (11th June 2019) - Elrefaey, A.; Pai, A.
Summary: An 80‐year‐old lady suffered loss of cardiac output during an elective pacemaker lead exchange. Right ventricular perforation, cardiac tamponade, vascular lacerations and circulatory shock are known major complications of pacemaker lead exchange and may necessitate aggressive resuscitation. An emergency sternotomy revealed the administered fluid, blood products and resuscitative drugs, which were administered through an upper limb cannula, had likely extravasated at the site of an iatrogenic injury to the superior vena cava. Unfortunately, further resuscitation attempts were unsuccessful. There are no recommendations regarding sites for intravascular access during pacemaker lead exchange and we argue that lower limb veins should be considered for venous access, as the superior vena cava and innominate veins are possible sites of unintentional vascular injury.